Ответы и объяснения

2013-05-20T10:41:31+00:00

2х-3y=-12

x+2y=1

  

2x-3y=-12

x+2y=1l*-2

 

2x-3y=-12

-2x-4y=-2

 

-2x+2x-3y-4y=-14

-7y=-14

y=2

x= 2x-3*(2)=-12

x=-6

 

 

3x+5y=2

6x+10y=4

 

3x+5y=2 l*-2

6x+10y=4

 

-6x-10y=-4

6x+10y=4

 

0=0 система решений не имеет

2013-05-20T10:45:16+00:00

2x-3y=-12           x=1-2y                                y=-14                       y=-14

x+2y=1                2(1-2y)-3y=-12                 x=1-2*(-14)              x=-27

                            2+4y-3y=-12

                            y=-12-2 

                            y=-14

                           

 

  

3x+5y=2             3x=2-5y                x=-1-5y                          x=-1-5*(-0/5)           x=1.5 

6x+10y=4           6x+10y=4            6(-1-5y)+10y=4           y=-0.5                       y=-0.5

                                                          -6-30y+10y=4

                                                        -30y+10y=4+6

                                                         -20y=10

                                                         y=-05